Checklist of helminths from lizards and amphisbaenians (Reptilia, Squamata) of south america - Ávila, R. W. [UNESP]; Silva, R. J. [UNESP] (FapUNIFESP (SciELO), 2010)
A comprehensive and up to date summary of the literature on the helminth parasites of lizards and amphisbaenians from South America is herein presented. One-hundred eighteen lizard species from twelve countries were reported in the literature harboring a total of 155 helminth species, being none acanthocephalans, 15 cestodes, 20 trematodes and 111 nematodes. Of these, one record was from Chile and French Guiana, three from Colombia, three from Uruguay, eight from Bolivia, nine from Surinam, 13 from Paraguay, 12 from Venezuela, 27 from Ecuador, 17 from Argentina, 39 from Peru and 103 from Brazil. The present list provides host, geographical distribution (with the respective biome, when possible), site of infection and references from the parasites. A systematic parasite-host list is also provided. © CEVAP 2010.
Keywords: Cestoda; Nematoda; Neotropical; Squamata; Trematoda